Impact of Ligand Structures on Precipitation Kinetics of Uranyl Nitrate Coordination Polymers with Diamide Linkers - Nojima Makito; Tsushima Satoru; Takao Koichiro (EPJ Web of Conferences)
The structure of uranyl nitrate complexes with four different diamide ligands with trans-1,4-cyclohexyl bridging moieties (two cyclic diamides (L1: γ-lactam, L2: δ-lactam) and two acyclic diamides with different linear chains (L3: Me, L4: Et)) and the effect of different ligand structures on the rate of precipitation formation were examined. L2, L3, and L4 formed 1D coordination polymers [UO2(NO3)2(Lx)]n (x = 2-4) in a similar manner to the previously reported case of L1. In use of the cyclic diamides, L1 and L2, the precipitation formation started right after loading these precipitants, and rapidly proceeded. On the other hand, use of the acyclic diamides, L3 and L4, exhibited induction period for more than the first 60 minutes prior to the precipitation formation, and even after that, slower precipitation rate was observed.